Chromatin structures condensed by linker histones. Issue 1 (22nd March 2019) - Zhou, Bing-Rui; Bai, Yawen
Abstract : In eukaryotic cells, genomic DNA exists in the form of chromatin through association with histone proteins, which consist of four core histone (H2A, H2B, H3, and H4) families and one linker histone (H1) family. The core histones bind to DNA to form the nucleosome, the recurring structural unit of chromatin. The linker histone binds to the nucleosome to form the next structural unit of chromatin, the chromatosome, which occurs dominantly in metazoans. Linker histones also play an essential role in condensing chromatin to form higher order structures. Unlike the core histones in the formation of the nucleosome, the role of linker histone in the formation of the chromatosome and high-order chromatin structure is not well understood. Nevertheless, exciting progress in the structural studies of chromatosomes and nucleosome arrays condensed by linker histones has been made in the last several years. In this mini-review, we discuss these recent experimental results and provide some perspectives for future studies.